CHARACTERISTICS OF PH AND NUMBER OF MICROBES IN THE RETICULUM, OMASUM AND ABOMASUM OF BALI CATTLE - I Gusti Ketut Suarjana; I Ketut Tono Pasek Gelgel; I Nengah Kerta Besung; Hapsari Mahatmi; Putu Henrywaesa Sudipa (Buletin Veteriner Udayana, 2024)
Bali cattle are native Indonesian cattle germplasm which must be preserved and cultivated. The research aims to determine the pH characteristics and number of microbes in the reticulum, omasum and abomasum of Bali cattle. The research sample was the stomach contents of the reticulum, omasum and abomasum of clinically healthy Bali cattle slaughtered at the slaughterhouse, Pesanggaran, Denpasar. Samples were taken aseptically from 30 cows. This research is observational with a cross-sectional study design. The number of bacterial and fungal colony populations was calculated using the pour plate method on nutrient agar plates and Sabouraud dextrose agar plates, respectively. The population of Enterobacteriaceae bacterial colonies was counted using the scatter method on Eosin Methylen Blue agar plates. pH measurements in cow stomach contents were carried out using pH indicator strips. The research data were analyzed descriptively. The results showed that the average pH of the reticulum, omasum and abomasum were 7,66; 6,50 and 5,26. The average total bacteria or ALTB in the reticulum, omasum and abomasum were 18,53 x 106 CFU/gr, 21,43 x 106 CFU/gr and 26,73 x 106 CFU/gr; the fungal population was 7,10 x 105 CFU/gr, 4,56 x 105 CFU/gr and 2,83 x 105 CFU/gr; Coliform counts were 60,03 x 103 CFU/gr, 57,70 x 103 CFU/gr and 61,60 x 103 CFU/gr; the number of non-Coliforms was 49,00 x 103 CFU/gr, 45,53 x 103 CFU/gr and 41,46 x 103 CFU/gr, the number of E.coli respectively 20,70 x 103 CFU/gr, 22, 83 x 103 CFU/gr and 22,86 x 103 CFU/gr.